Plädoyer für ein Investitionsprogramm gegen Langzeitarbeitslosigkeit - Alexander Spermann (Wirtschaftsdienst, 2015)
Am 5. November 2014 legte die Bundesarbeitsministerin unter dem Titel 'Chancen eröffnen: soziale Teilhabe sichern' ein Konzept zum Abbau der Langzeitarbeitslosigkeit vor. Insbesondere anhand von Einzelfällen lässt sich allerdings zeigen, dass Langzeitarbeitslose in den Jobcentern nur unzureichend betreut werden. Diese Gruppe von Arbeitsuchenden wieder in den ersten Arbeitsmarkt einzugliedern, sollte vordringliches Ziel der Arbeitsvermittlung sein. Der Autor stellt ein Fünf-Säulen-Konzept vor, das auf Prävention und intensive Betreuung der Langzeitarbeitslosen setzt. – – The number of long-term unemployed people in Germany has stagnated at around one million for many years. Despite excellent labour market conditions, the long-term unemployment rate is well above the OECD national average. The principle of 'encourage and challenge', which was implemented in 2005 along with the Hartz IV reform, is in clear need of further development. What needs to be done to actually help the long-term unemployed? The author proposes a five-pillar concept for preventing and reducing long-term unemployment and long-term receipt of benefits. An activation strategy for the long-term unemployed and long-term benefit recipients requires more and better trained case managers in the job centres as well as social integration services (debt, addiction and psychosocial counselling) that are available nationwide.
Keywords: J24; J31; J38; 330; Langzeitarbeitslosigkeit; Arbeitsvermittlung; Arbeitsmarktintegration; Deutschland